2022
DOI: 10.3390/jcm11143966
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Etiology and Auditory Profiles in Infants with Congenital Unilateral Sensorineural Hearing Loss

Abstract: Congenital unilateral sensorineural hearing loss (uSNHL) is associated with speech-language delays and academic difficulties. Yet, controversy exists in the choice of diagnosis and intervention methods. A cross-sectional prospective design was used to study hearing loss cause in twenty infants with congenital uSNHL consecutively recruited from a universal neonatal hearing-screening program. All normal-hearing ears showed ≤20 dB nHL auditory brainstem response (ABR) thresholds (ABRthrs). The impaired ear median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 68 publications
(149 reference statements)
2
24
1
Order By: Relevance
“…For patients without a definite genetic diagnosis in this study, CND accounted for 64.3% of their etiologies, and cCMV infection was responsible for a small proportion of USNHL cases (Supplemental Figure S1). Our results are compatible with previous findings that CND and inner ear malformations are common causes of USNHL 48 . Nevertheless, there may still be genetic determinants that underlie these two origins.…”
Section: Discussionsupporting
confidence: 93%
“…For patients without a definite genetic diagnosis in this study, CND accounted for 64.3% of their etiologies, and cCMV infection was responsible for a small proportion of USNHL cases (Supplemental Figure S1). Our results are compatible with previous findings that CND and inner ear malformations are common causes of USNHL 48 . Nevertheless, there may still be genetic determinants that underlie these two origins.…”
Section: Discussionsupporting
confidence: 93%
“…However, three subjects did not like to, or could not, complete or participate in the MRI, which limits the conclusions possible to draw from the MRI. (For a completely different study group, the congenital unilateral SNHL as identified at birth, MRI revealed malformations in 64% of all scans [ 93 ].)…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were recruited from a UNHS program based on multiple transient-evoked otoacoustic emission (TEOAE) recordings and an automatic auditory brainstem response (aABR) (Region Stockholm, years 2019–2020, newborns screened estimated to ≈51,600 [ 20 ]). The UNHS program [ 2 , 20 , 21 , 22 , 23 ], and the multiple steps that were undertaken to invite all children with uSNHL born during this 2 year period have been described in detail elsewhere [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results of the auditory tests (ABRs, TEOAEs, distortion-product OAEs (DPOAEs), tympanograms, and acoustic reflex thresholds (ARTs)), and congenital cytomegalovirus (CMV) infection testing at the first visit has been described previously [ 20 ]. An experienced otologist also performed otomicroscopy on all subjects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation